Delayed Right-Sided Traumatic Diaphragmatic Rupture Complicated by Hepatothorax and Visceral Herniation a Decade Post-Trauma: A Case Report - Mada Aji Prakoso; Albertus Ari Adrianto; Parish Budiono (HM Publisher, 2026)
Background: Traumatic diaphragmatic rupture (TDR) is a rare consequence of high-energy blunt trauma, accounting for less than 1% of all traumatic injuries. Right-sided ruptures are particularly uncommon, representing only 5% to 20% of cases, largely due to the protective anatomical positioning of the liver. Consequently, right-sided injuries are notoriously difficult to detect, often leading to a delayed diagnosis. Case presentation: We present the case of a 29-year-old female who presented with progressive dyspnea ten years after sustaining a motor vehicle collision. Her initial injury was managed as a right-sided hemothorax, with the diaphragmatic defect remaining undetected. A decade later, imaging revealed an elevated right hemidiaphragm with massive herniation of the liver, gallbladder, transverse colon, and omentum into the right thoracic cavity. The patient underwent a successful abdomino-thoracotomy with primary repair of a 10 cm x 4 cm defect, reinforced with a prosthetic mesh. She was discharged on postoperative day seven with an uneventful recovery. Conclusion: This case emphatically highlights the persistent, lifelong risk of delayed visceral herniation following thoracoabdominal trauma. A high index of suspicion must be maintained for patients presenting with delayed respiratory symptoms, as prompt surgical intervention yields excellent outcomes.